Imaging of Integrins as Biomarkers for Tumor Angiogenesis - Cai, Weibo; Niu, Gang; Chen, Xiaoyuan (Current Pharmaceutical Design, 2008)
The integrin family plays important roles during tumor angiogenesis, the formation of new blood vessels from pre-existing vasculature. Traditional structural and functional imaging techniques are not sufficient for early lesion detection, patient stratification, or monitoring the therapeutic efficacy against cancer. Molecular imaging, the visualization, characterization and measurement of biological processes at the molecular and cellular levels in humans and other living systems, can fulfill these goals. In this review article, we will summarize the current state-of-the-art of imaging integrin (α2β1, α3β1, α4β1, αvβ3, and αvβ6) expression using either single molecular imaging modality (magnetic resonance imaging, untrasound, optical, single photon emission computed tomography, and positron emissiom tomography) or a combination of different modalities. For clinical translation, radionuclide-based imaging will have broad potential applications in cancer patients and the currently available clinical data (exclusively on integrin αvβ3 so far) will be discussed in detail. The design, optimization, and characterization of imaging agents targeting integrins will be presented and areas needing extensive future research effort will be discussed. In the new era of personalized medicine, fast clinical translation and incorporation of integrin imaging into anti-cancer clinical trials will be critical for the maximum benefit of cancer patients.
Keywords: Angiogenesis